Optimization of drill geometry design for orthopedic surgical application in dry drilling condition - Mohd Samsuddin, Noorazizi (2017)
During a routine orthopedic surgery, the principle biomechanical procedure in repairing and reconstructing bone fractures is done by drilling the bone, fixing and re-attaching the separate parts using screws, wires, and plates. Such a procedure is usually performed manually with a hand-held surgical tool. Hitherto, the rate of success of these surgeries varies significantly and often highly dependent on the surgeons’ skills. Medical tool designers have always neglected this important factor in their designs. Common scenarios of imprecise manipulations or deviations from normal drill axis can cause the drill to skid across the bone surface. These maladjustments affect the hole accuracy, which then leads to a localized temperature rise resulting in thermal necrosis of the soft tissues surrounding the hole region. Many different surgical drill bit designs and geometries have been proposed over the years, each with its own claim of success. However, most of the drills are based on normal 0 degree penetration angle which does not represent the realistic angle of manually controlled penetrations by surgeons. In drilling mechanics, a deviation of 1 degree of penetration angle from the normal bone surface will result in frictions increment which then would antagonize the hole performance. Recognizing the importance of studying this phenomenon, this research develops a new surgical drill bit design to solve the discrepancies during orthopedic surgeries. The development of the new drill design is achieved through the combination of the in-vitro experimental work and statistical optimization technique. A total of 17 different drill designs with varied helix angle, point angle, and web thickness were fabricated and tested on drilling bovine femur cortical bone at different penetration angles. The effects of each factor on the hole accuracy, surface roughness, drilling force and drilling temperature were considered as the desired response that needs to be achieved for the new drill design. From the investigation, the most significant parameter that affects the hole performance was the penetration angle followed by the point angle. Also, the interaction between helix angle and web thickness controlled the drilling performance. Through statistical optimization analysis, the selected optimum drill geometry angles that score the highest desirability based on 30° penetration angle condition was (25% web thickness, 107.0° point angle, and 35.0° helix angle). The new optimum drill design was fabricated and followed by a set of validating experimental works that produced less than 10% error which confirms its validity. The proposition of a new geometric design for surgical drill bits that takes into account of up to 30° drilling penetration angle deviations will further catalyze breakthrough advancements in biomechanical and biomedical technologies.